Mhenni: An Online Marketplace for On-demand Services - Mohamed Nafea, Baza; Chahrazed, Bouzahar; Noureddine Amraoui: Reporter (Mohamed Boudiaf University of M'sila, 2024)
This report presents Mhenni, an online marketplace for on-demand services such as home and transportation services. Mhenni bridges the current gap in the Algerian market between service providers and customers. On one hand, Mhenni gives providers the opportunity to offer their services to potential customers and showcase their skills and accumulate reviews and ratings. On the other hand, customers can effortlessly find providers, schedule appointments, negotiate prices, and manage their budgets. This report provides a comprehensive technical documentation of the system. First of all, in the business analysis stage, we have documented the process of collecting relevant information about system requirements and studying the life cycle of a service from the moment being created until being served. In the design stage, we provided a detailed description of the system in terms of architecture and behavior. The implementation and deployment of Mhenni’s proof of concept has been documented as well by presenting different development and deployment technologies.
Keywords: Online Marketplace; On-demand Services